RANCANG BANGUN ALAT DETEKSI KEBAKARAN BERBASIS MIKROKONTROLER ESP32 DENGAN ENERGI SURYA - Naibaho, Nurhabibah; Ramadhan, Arlan (JURNAL ELEKTRO, 2025)
Fires are disasters that can cause significant material and non-material losses. Therefore, an effective and efficient fire detection system is needed. This study aims to design and develop a fire detection system based on the ESP32 microcontroller with advanced sensors and monitoring technology. The system uses a flame sensor to detect fire, a DHT22 sensor to monitor temperature and humidity, an MQ-135 sensor to detect smoke, and a Ublox Neo-6M GPS module to determine the location of the fire. Sensor data is sent to the Blynk application for real-time monitoring, and the system uses solar energy as the primary power source. Additionally, the system is equipped with an emergency button to send distress signals and a siren for early warning. Testing results show that the flame sensor detects fire up to a maximum distance of 105 cm, indicated by a red LED light and the siren sounding. The MQ-135 sensor shows an increase in ppm levels on the Blynk application when smoke is present, with the siren activating when the ppm level exceeds 2000. The DHT22 sensor has high accuracy, with an error of 2.96% for temperature and 2.7% for humidity when tested with a Thermohygrometer. The GPS module provides accurate location information when a fire is detected. The Blynk application successfully displays real-time sensor data and sends fire detection notifications. The solar power system charges the battery with an average voltage of 12.2 Volts and a current of 0.46 Amps, with the battery voltage gradually decreasing by 0.5 Volts. This system can detect fires quickly and accurately, provide precise location information, and issue early warnings, thus aiding in early fire response and minimizing losses.